Planes : fire & rescue [videorecording (Blu-Ray + DVD)] - Gannaway, Bobs; Howard, Jeffrey M., 1969-; Cook, Dane; Harris, Ed, 1950-; Bowen, Julie; Armstrong, Curtis; Higgins, John Michael; Holbrook, Hal; Studi, Wes; Garrett, Brad, 1960-; Hatcher, Teri; Keach, Stacy; et al. (Disney Blu-ray., 2014)
"When world-famous air racer Dusty learns that he may never race again, he must shift gears and is launched into the world of aerial firefighting"--Container.